Respiratory impedance is correlated with airway narrowing in asthma using three‐dimensional computed tomography. Issue 3 (5th February 2018) - Karayama, M.; Inui, N.; Mori, K.; Kono, M.; Hozumi, H.; Suzuki, Y.; Furuhashi, K.; Hashimoto, D.; Enomoto, N.; Fujisawa, T.; Nakamura, Y.; Watanabe, H.; et al.
Summary: Background: Respiratory impedance comprises the resistance and reactance of the respiratory system and can provide detailed information on respiratory function. However, details of the relationship between impedance and morphological airway changes in asthma are unknown. Objective: We aimed to evaluate the correlation between imaging‐based airway changes and respiratory impedance in patients with asthma. Methods: Respiratory impedance and spirometric data were evaluated in 72 patients with asthma and 29 reference subjects. We measured the intraluminal area (Ai) and wall thickness (WT) of third‐ to sixth‐generation bronchi using three‐dimensional computed tomographic analyses, and values were adjusted by body surface area (BSA, Ai/BSA, and WT/the square root (√) of BSA). Results: Asthma patients had significantly increased respiratory impedance, decreased Ai/BSA, and increased WT/√BSA, as was the case in those without airflow limitation as assessed by spirometry. Ai/BSA was inversely correlated with respiratory resistance at 5 Hz (R5) and 20 Hz (R20). R20 had a stronger correlation with Ai/BSA than did R5. Ai/BSA was positively correlated with forced expiratory volume in 1 second/forced vital capacity ratio, percentage predicted forced expiratory volume in 1 second, and percentage predicted mid‐expiratory flow. WT/√BSA had no significant correlation with spirometry or respiratory impedance. Conclusions & Clinical Relevance: Respiratory resistance is associated with airway narrowing.